Phylogenetic and expression analysis of terpenoid synthase gene family in Eustoma grandiflorum - LI Xinyuan; LIANG Yuwei; FANG Huiyi; SUN Fuhui; ZHANG Liangsheng (浙江大学学报. 农业与生命科学版, 2024)
Terpenoids are one of the main components of floral fragrance, and terpenoid synthase (TPS) plays a key role in the synthesis of terpenoids. In this study, 26 full-length TPS genes were identified using bioinformatics methods, and their molecular evolution, gene structure, and expression patterns were analyzed. The results revealed that the TPS genes of Eustoma grandiflorum could be classified into five subfamilies (TPS-a, TPS-b, TPS-g, TPS-e, and TPS-f), which were further divided into 10 smaller clades. Among these clades, only the TPS-a.1 clade exhibited amplification, while most of the other clades presented gene loss. Collinearity analysis of genes demonstrated that five collinear gene pairs were formed through two recent whole genome duplication events in E. grandiflorum, and most of the TPS genes were lost, further supporting the conclusion that most TPS genes in E. grandiflorum have been lost. Transcriptome expression analysis showed that only EgTPS-g1, EgTPS-g2, and EgTPS-g3 were expressed in the early stages of petal development, and TPS-a and TPS-b subfamily members were not expressed in the petals of E. grandiflorum, likely contributing to the lack of floral fragrance. Future research should focus on TPS-a and TPS-b subfamily members and restore the expression of these subfamily genes, which are expected to give the floral fragrance to E. grandiflorum and thus improve its ornamental value.